2005
DOI: 10.1093/ajcn/82.4.740
|View full text |Cite
|
Sign up to set email alerts
|

Relation of weight maintenance and dietary restraint to peroxisome proliferator–activated receptor γ2, glucocorticoid receptor, and ciliary neurotrophic factor polymorphisms

Abstract: The different genotypes of the PPARgamma2 and GRL genes contribute to WM, either directly (GRL) or indirectly (PPARgamma2 and GRL) via baseline body mass index and waist circumference, and to changes in Three-Factor Eating Questionnaire scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 44 publications
2
26
1
1
Order By: Relevance
“…They observed that both carrying the Ala allele and the amount of fat oxidation reduction were predictors of weight regain. This finding was confirmed by Vogels et al [50], who identified proportionally more Ala-allele carriers among subjects with unsuccessful (23.5%) than with successful (9.5%) weight maintenance. The Ala variant of the protein has lower binding affinity for the promoter element of target genes, which is accompanied by a lower transactivation [77], in that case fat oxidation.…”
Section: Genetic Predispositionsupporting
confidence: 65%
See 2 more Smart Citations
“…They observed that both carrying the Ala allele and the amount of fat oxidation reduction were predictors of weight regain. This finding was confirmed by Vogels et al [50], who identified proportionally more Ala-allele carriers among subjects with unsuccessful (23.5%) than with successful (9.5%) weight maintenance. The Ala variant of the protein has lower binding affinity for the promoter element of target genes, which is accompanied by a lower transactivation [77], in that case fat oxidation.…”
Section: Genetic Predispositionsupporting
confidence: 65%
“…On the other hand, conflicting findings have been reported as well. Vogels et al [50] measured the leptin drop in successful and non-successful weight maintainers after weight loss by a 6-week VLCD. The unsuccessful group (n = 99) lost 7.2 kg body weight (4.6 kg fat mass) and regained 4.9 kg within 1 year, whereas the successful group (n = 21) lost a comparable 7.6 kg body weight (4.9 kg fat mass) and lost an additional 1.8 kg.…”
Section: Module 2: Energy Regulation By Metabolic Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the current strategies to improve weight maintenance are focused on comparing the genetic make up and potential interactions with the dietary intake [20,[32][33][34] . However, only a few investigations have evaluated the predictive role of nutrigenomics on weight regulation and weight cycling [19] .…”
Section: Discussionmentioning
confidence: 99%
“…So, in order to dismiss this heterogeneity, body weight changes, concretely those related to the maintenance period, were considered taking into account the cut-off point of the 10% body weight loss re- gain. Thus, subjects were categorized into 2 distinct groups (WMS and WRS) according to either high or low weight change during the 6-month weight-maintenance period [20,34] . Firstly, we analyzed the influence of weight maintenance in the anthropometrical variables, which revealed no differences before and after the LCD.…”
Section: Discussionmentioning
confidence: 99%